MOTIVASI KERJA SEORANG CPNS DISABILITAS BAGIAN REHABILITASI SOSIAL DI DINAS SOSIAL KABUPATEN KEDIRI - Andrian, Noval (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2022)
This study aims to identify, assess and explain the motivational experience experienced by a civil servant with a disability in order to motivate everyone, especially people with disabilities, to keep the enthusiasm and motivation to work for survival. Motivation can arise through internal and external factors. Internal appears in oneself which is characterized by having a strong mindset and mentality so that a sense of enthusiasm can grow in oneself. External factors arise from the surrounding environment, relatives, friends, circumstances / conditions. This study uses a qualitative method with a case study approach (single case). The case study approach is used because it focuses on exploring food experiences to get learning motivation for a civil servant with a disability in the social rehabilitation section of the Social Service of Kediri Regency. The results of the study show that disability is a physical limitation possessed by a person with a different body shape that is not perfect so that they have different abilities from individuals in general. Here, a civil servant with a disability at the social service office of the Kediri Regency has a high work motivation where with his physical limitations he still does a good job, and even has a responsive spirit which not everyone has it. This shows that everyone has the right to fulfill their wants and needs and has motivation.